Spirometric Values of Patients with Chronic Obstructive Pulmonary Disease in Dr. Hasan Sadikin General Hospital Bandung - Christopher Rinaldi; Rudolf Andean; Irma Ruslina Defi (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Chronic obstructive pulmonary disease (COPD) is a frequently underdiagnosed disease. Definitive COPD has been diagnosed using spirometry to evaluate pulmonary function. This study aimed to explore the spirometric values of COPD patients to aid in the diagnosis of COPD.Methods: A descriptive study was conducted in Dr. Hasan Sadikin General Hospital Bandung from October to November 2015. Data on patients diagnosed with COPD, aged 40 to 60 years old, were collected during the year 2014 prior to ethical clearance. Spirometry values consisted of forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and FEV1/FVC ratio were taken from the medical records.Results: Sixty-eight COPD patients, consisting of 48 males and 20 females, were included of with most were classified as moderate COPD. The FEV1 was 49.72±17.79, whereas the FVC was 55.90 (range 22.80–96.03), and the FEV1/FVC ratio was 0.70±0.12. Most patients were classified into moderate COPD who had FEV1 between 50 and 80% of normal as GOLD 2 standard.Conclusions: Even though patients seem to have no symptoms, spirometric values may show a silent insufficient lung function affecting patients’ daily life.